Maritime Sustainability Best Paper Award - Zis, Thalis (My University, 2026)
During the 2020 IAME conference (held virtually in Hong Kong), my paper was selected as the best conference paper in maritime sustainability. This was a monograph, with research based on the PortGreen project (funded by the Orietns Fund).
Keywords: Arts and entertainment